Moderate and severe perinatal asphyxia induces differential effects on cocaine sensitization in adult rats - Galeano, Pablo (2013)
Perinatal asphyxia (PA) increases the likelihood of suffering from dopamine related disorders, such as ADHD and schizophrenia. Since dopaminergic transmission plays a major role in cocaine sensitization, the purpose of this study was to determine whether PA could be associated with altered behavioral sensitization to cocaine. To this end, adult rats born vaginally (CTL), by caesarean section (C+), or by C+ with 15 min (PA15, moderate PA) or 19 min (PA19, severe PA) of global anoxia were repeatedly administered with cocaine (i.p., 15 mg/kg) and then challenged with cocaine (i.p., 15 mg/kg) after a five day withdrawal period. In addition, c-Fos, FosB/deltaFosB, DAT and TH expression were assessed in dorsal (CPu) and ventral (NAcc) striatum. Results indicated that PA15 rats exhibited an increased locomotor sensitization to cocaine, while PA19 rats displayed an abnormal acquisition of locomotor sensitization and did not express a sensitized response to cocaine. c-Fos expression in NAcc, but not in CPu, was associated with these alterations in cocaine sensitization. FosB/deltaFosB expression was increased in all groups and regions after repeated cocaine administration, although it reached lower expression levels in PA19 rats. In CTL, C+ and PA15, but not in PA19 rats, the expression of TH in NAcc was reduced in groups repeatedly treated with cocaine, independently of the challenge test. Furthermore, this reduction was more pronounced in PA15 rats. DAT expression remained unaltered in all groups and regions studied. These results suggest that moderate PA may increase the vulnerability to drug abuse and in particular to cocaine addiction.